2019
DOI: 10.1016/bs.asb.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection in socially-structured, polyandrous populations: Some insights from the fowl

Abstract: Sexual selection is widely recognised as the evolutionary agent driving male exaggeration and strategies of intrasexual competition over reproductive opportunities. Two advances have characterised the development of our understanding of sexual selection in recent years. The first was the realisation that sexual selection can extend to postcopulatory episodes whenever females mate with multiple males (polyandry). The second concerns the operation of sexual selection in structured population in light of increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 222 publications
(311 reference statements)
3
20
0
1
Order By: Relevance
“…The assumptions about evolutionary costs and benefits of dominance interactions, described in the Methods section, entail that reproductive success on average increases linearly with the dominance position, from lowest to highest. The effect of the dominance position on reproductive success might well vary between species and situations, and is often not empirically estimated in detail, but the model assumptions are at least broadly consistent with what is known about male fowl (McDonald et al, 2017;Pizzari and McDonald, 2019). The result for male fowl that experimentally induced wins or losses had rather little influence on subsequent hierarchy formation (Favati et al, 2017) is also broadly consistent with the model.…”
Section: )mentioning
confidence: 79%
See 1 more Smart Citation
“…The assumptions about evolutionary costs and benefits of dominance interactions, described in the Methods section, entail that reproductive success on average increases linearly with the dominance position, from lowest to highest. The effect of the dominance position on reproductive success might well vary between species and situations, and is often not empirically estimated in detail, but the model assumptions are at least broadly consistent with what is known about male fowl (McDonald et al, 2017;Pizzari and McDonald, 2019). The result for male fowl that experimentally induced wins or losses had rather little influence on subsequent hierarchy formation (Favati et al, 2017) is also broadly consistent with the model.…”
Section: )mentioning
confidence: 79%
“…The model is meant to be general, but still makes assumptions about cognitive capacities and how fitness depends on social interactions during a life history. As a possible example, one might consider interactions in groups of fowl (Schjelderup-Ebbe, 1922), in particular groups of male fowl (Pizzari and McDonald, 2019), in which individuals both display and fight during hierarchy formation.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of remating by many males may occur for two non-mutually exclusive reasons. (i) It may take some time for the social hierarchies to influence differential access to mating opportunities, and mating later in the trial may become increasingly difficult for low-ranking males, as dominant males progressively monopolize females [60]. Consistent with this, dominant males were more likely to fertilize eggs on the eighth day of the trial (see Analysing each day of the trial separately, in the electronic supplementary material).…”
Section: Discussionmentioning
confidence: 94%
“…These mechanisms can be modulated by characteristics of individual males and females, and their interactions. For example, male social status mediates competitive access to mates and mating opportunities, and is favoured by female responses before and after mating [60]. On the other hand, male status may be negatively related to sperm fertilizing efficiency [46,67], as observed in species with more distinct alternative mating tactics [68,69], suggesting a possible trade-off between male investment in pre-versus post-copulatory intrasexual competition.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, low-ranking males may suffer from limited access to food and other resources; on the other hand, high-ranking males may face higher energetic costs to maintain dominant status via aggressive interactions. Dominant males also invest less time feeding and resting than subordinate males (Pizzari & McDonald, 2019), suggesting that over time, high-ranking males may be prone to lose weight. In addition, several studies have shown a female preference to mate with males sporting a large comb (a fleshy head ornament; reviewed in Parker & Ligon, 2002;Pizzari & McDonald, 2019).…”
mentioning
confidence: 99%